THE EFFECT OF LEARNING MOTIVATION, LEARNING READINESS, AND PEER GROUP ON LEARNING OUTCOMES THE BASICS OF ACCOUNTING GRADE X ACCOUNTING STUDENTS IN SMK NEGERI 1 BOGOR - Widiawati, Shinta; Zulaihati, Sri; Fauzi, Achmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
This study aims to determine the relationship effect of learning motivation, learning readines, and peergroup on learning outcomes of class x accounting state vocational high school 1 Bogor on subjects tobasic accounting, both partially and simultaneously. This study uses a survey method with a correlationapproach. The affordable population in this study was 105 students. The sampling technique usespropotional random sampling so that a sample of 83 students is obtained. From the requirements of theanalysis carried out, the data are stated to be normally distributed and linear with multipleregression equation Ῡ= 44,839 + 0,130X1 + 0,126X2 + 0,129X3. Obtained a multiple correlation coefficientof 0.393 and the coefficient of determination 15.4% thus the hypothesis is accepted. Then, based on theresults of the test analysis that has been done, the learning outcomes are influenced by learningmotivation, learning readinesss, and peer group.